In-line rheo-optical characterization of extruded complex fluids - Thepthong, S. (2011)
We present here results of a Master thesis [1] carried out in the frame of EURHEO: the Erasmus Mundus Master in Engineering Rheology, which is a Master programme funded by the European Union (EACEA) and described elsewhere in these proceedings. Driven by the need of in-line monitoring of extrusion based processes, and by the necessity of better understanding the interplay between such process and the extrusion-induced structures in polymer engineering, a specific rheooptical slit device has been designed that allows the optical and rheological characterization of materials coming out of a mini-extrusion line which operates in the output range of tens of grams per hour, as opposed to kgs per hour outputs conventionally found in lab-scale extrusion machines. We first present the rheological and optical validation of the device, and then briefly show a set of result obtained with a model polymer blend.